Production efficiency of linseed varieties under organic management condition in mild hills of Sikkim Himalayas: Production efficiency of linseed varieties under organic management condition in mild hills of Sikkim Himalayas - AMIT KUMAR; R SINGH; SUBHASH BABU; R K AVASTHE; R G LAHA; V K MISHRA; E L DEVI; A AZIZ QURESHI; A L RATHNAKUMAR; DIVYA AMBATI; M SUJATHA; S K PRASAD (Journal of Oilseeds Research, 2023)
Six linseed varieties viz., RLC 153, Sekhar, LSC-93, Priyam, JSL-95 and T-395 were evaluated at Research Farm of ICAR Research Complex for NEH Region Sikkim Centre, Tadong, Gangtok, Sikkim during Rabi season of 2021-22 in a randomized complete block design (RCBD) with four replications under organic management condition. The results indicated that significantly maximum number of bolls/plant and number of seeds/boll was observed in Priyam followed by LSC-93. Maximum 1000 seed weight was noticed under LSC-93 which was statistically a par with JSL-95 and significantly higher than other varieties. Significantly highest seed yield was recorded in Priyam followed by LSC-93, RLC-153 and may be recommended for cultivation by farmers of Sikkim Himalayas and similar agro-ecoregions under organic production system.